The intensive care unit--who's in charge? The private practice view - Trask, A L; Faber, D R (Archives of surgery (Chicago. 1960), 1990)
In the past 10 years, a number of authors have expressed concern that surgeons are abdicating their traditional role of providing preoperative and postoperative care in surgical intensive care units. To study today's private practice environment, we took a survey. Questionnaires were sent to the chiefs of surgery and the nurse managers of the surgical intensive care units at 188 non-university-affiliated hospitals throughout the United States. Results show that surgeons do not have the principal managing role in the intensive care unit for surgical patients in 70% to 75% of the hospitals. Results also indicated that surgeons are relinquishing their responsibilities in the direct care of the preoperative and postoperative critically ill patients. Three main reasons are given for this: (1) an ever-increasing body of critical care knowledge plus complex technology, (2) a lack of economic incentive, and (3) professional liability. To reverse this trend, these three areas must be addressed.